Difference Analysis of Major Quality Components in Different Turning over Intensities of Chungui Oolong Tea in Northern Fujian - Xinyi ZHAN; Yun YANG; Bin CHEN; Huiqing HUANG; Mengying ZHAO; Xinlei LI; Yun SUN (Shipin gongye ke-ji, 2023)
In order to explore the processing technology characteristics of northern Fujian oolong tea processed by Chungui variety, sensory evaluation, biochemical analysis, ultra-performance liquid chromatography-triple quadrupole tandem mass spectrometry (UPLC-QqQ-MS) and headspace solid-phase microextraction combined with gas chromatography-time of flight mass spectrometry (HS-SPME-GC-TOF-MS) were used to investigate the differences in sensory quality, physicochemical quality, catechin fraction, amino acid fraction and volatile substances of northern Fujian oolong tea at different turning over intensities. The results showed that the light turning over intensity treatment had tight shape, with a distinctive floral aroma and fresh taste, and the total score of sensory quality was 90.6, and heavy turning over intensity treatment had slightly loose shape, floral fragrance and a strong mellow taste, sensory score 88.0. The catechin components were all significantly higher in the light turning over intensity treatment of Chungui than heavy turning over intensity treatment (P<0.05). The amino acid content of the light turning over intensity treatment was generally higher than that of the heavy turning over intensity treatment, with highly significant differences in the content of glutamine and arginine (P<0.01), and a greater reduction in the content of theanine and glutamate. As the degree of turning over intensity increased, the contents of nerolidol, geraniol, caprylate, benzyl alcohol and caprylate increased significantly (P<0.05) and the contents of indole, α-farnesene, jasmonolactone, phenethyl alcohol, dihydrokiwiolactone and dehydrolinalool decreased significantly (P<0.05). In conclusion, the light turning over intensity treatment of Chungui tea, tea soup taste fresh, strong convergence, high aroma and flowers and fruits fragrance, tea polyphenols, catechins and amino acids content, the heavy turning over intensity treatment resulted in a rich and mellow taste with good sweetness, rich and floral aroma, high flavonoid content and a significant decrease in catechin and amino acid. This study can provide a theoretical basis for the processing oriented quality control of Chungui oolong tea in northern Fujian.